The limitations of diversity metrics in directing global marine conservation - Robinson,James PW; White,Easton R; Wiwchar,Logan D; Claar,Danielle C; Suraci,Justin P; Baum,Julia K (PeerJ PrePrints, 2014)
Biodiversity hotspots have been used extensively in setting conservation priorities for reef ecosystems. A recent Nature publication claims to have uncovered new hotspots based on global comparisons of functional diversity. Simulation models show that the purported novel evenness pattern is a mathematical inevitability of differences in species richness, as well as an artefact of differences in detectability between vastly different marine ecosystems. Constraints on evenness, along with disparity among communities in possible functional traits, cast doubt on the utility of global functional diversity comparisons for management of marine systems.
Keywords: diversity hotspots; functional diversity; conservation; marine fish; evenness; reef ecosystems